2023
DOI: 10.3389/fnmol.2022.1025066
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of an evodiamine derivative for PI3K/AKT/GSK3β pathway activation and AD pathology improvement in mouse models

Abstract: Alzheimer's disease (AD) is a neurodegenerative disease characterized by progressive neurodegeneration and cognitive decline. Evodiamine, a main component in Chinese medicine, was found to improve cognitive impairment in AD model mice based on several intensive studies. However, evodiamine has high cytotoxicity and poor bioactivity. In this study, several evodiamine derivatives were synthesized via heterocyclic substitution and amide introduction and screened for cytotoxicity and antioxidant capacity. Under th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Furthermore, recent studies have demonstrated that evodiamine derivatives can activate the phosphoinositide 3‐kinase / protein kinase B / glycogen synthase kinase 3β (PI3K/AKT/GSK3β) pathway, exerting their activity against H 2 O 2 and Aβ oligomers (AβOs). This activity significantly improves working memory and spatial memory in 3xTg and amyloid precursor protein (APP)/PS1 transgenic mice 14 . These findings suggest the potential therapeutic effect of evodiamine in AD.…”
Section: Current Status Of the Main Alkaloid Components Of Evodia In ...mentioning
confidence: 75%
See 1 more Smart Citation
“…Furthermore, recent studies have demonstrated that evodiamine derivatives can activate the phosphoinositide 3‐kinase / protein kinase B / glycogen synthase kinase 3β (PI3K/AKT/GSK3β) pathway, exerting their activity against H 2 O 2 and Aβ oligomers (AβOs). This activity significantly improves working memory and spatial memory in 3xTg and amyloid precursor protein (APP)/PS1 transgenic mice 14 . These findings suggest the potential therapeutic effect of evodiamine in AD.…”
Section: Current Status Of the Main Alkaloid Components Of Evodia In ...mentioning
confidence: 75%
“…This activity significantly improves working memory and spatial memory in 3xTg and amyloid precursor protein (APP)/PS1 transgenic mice. 14 These findings suggest the potential therapeutic effect of evodiamine in AD.…”
Section: Current Status Of the Main Alkaloid Components Of Evodia In ...mentioning
confidence: 85%
“…Evodiamine (EVO) is an indolequinone alkaloid derived from Evodia rutaecarpa 5 . EVO is composed of a pentacyclic structure including three nitrogen atoms and exhibits abundant pharmacological potential including anti-cancer 6 , anti-bacterial 7 , and anti-neurodegenerative 8 , anti-inflammatory 9 , anti-obesity 10 , anti-depressant 11 and cardioprotective 12 . Furthermore, reported studies demonstrated that it has a promising anticancer property by specifically inducing apoptosis and cell cycle arrest, reducing cell proliferation and inhibiting metastasis in cancer cells 13 15 .…”
Section: Introductionmentioning
confidence: 99%
“…International research on traditional Chinese medicine for the treatment of AD has focused on Chinese herbs [e.g., Morinda officinalis How , Astragali radix (Dong et al, 2022)] or active ingredients of Chinese herbs [e.g., polysaccharides , ginsenoside (Wu et al, 2022a), evodiamine (Pang et al, 2022), Huperzine A (Yan et al, 2022)], herbal prescriptions [e.g., Yi-Gan San (Yang et al, 2023), Yuan-Zhi Decoction (Wu et al, 2022b)], special therapies [e.g., Wuqinxi exercise (Luo et al, 2022), Tai Chi Quan (Wang et al, 2022)], and acupuncture (Cai et al, 2019;Yu et al, 2021a;Zheng et al, 2021;Hao et al, 2022) to improve memory and cognitive impairment in AD models, involving various mechanisms such as regulation of βamyloid and tau proteins, anti-oxidation, anti-neuroinflammation, modulation of autophagy and many other mechanisms. Among these, acupuncture is considered to be a highly promising alternative therapy for AD.…”
Section: Discussionmentioning
confidence: 99%